PRESCHOOL EDUCATIONAL ORGANIZATION FORMATION OF CHILDREN'S ADAPTATION SKILLS - Rozikova Gulchehra Hazratkulovna (Journal Park Publishing, 2023)
This article covers the adaptation of children to preschool education in the organization and the formation of skills.
Keywords: adaptation, preschool educational organization, family, educator.